Exciton photon coupling in all-inorganic cesium lead halide perovskite microcavities - Su, Rui (2019)
All-inorganic cesium lead halide perovskites are emergent semiconductors as excellent light emitters. With the ease of synthesis, high quantum efficiency, large absorption coefficient and seamlessly tunable bandgap, all-inorganic cesium lead halide perovskites are regarded as ideal semiconductor system to compensate traditional semiconductors towards high performance optoelectronic applications. In this thesis, I mainly focus on investigating light-matter interaction properties in cesium lead halide perovskites towards future optoelectronic applications. The investigation starts from the synthesis of all-inorganic cesium lead halide perovskite crystals with excellent quality. A van der Waals (vdW) epitaxy technique is introduced in synthesizing all-inorganic cesium lead halide perovskite crystals based on a one-step vapor phase synthesis method. High quality cesium lead halide perovskite nanoplatelet crystals and large films can be obtained with excellent crystallinity and strong emissions. The emission of cesium lead halide perovskites can be seamlessly tuned from 1.7 eV to 3.0 eV by composition modulations. Most of the cesium lead halide perovskites are confirmed to possess stale excitons at room temperature by the absorption spectroscopy. Large exciton binding energies of ~ 37 meV for CsPbBr3 and ~ 70 meV for CsPbCl3 are extracted from the analysis of temperature-dependent exciton absorption peak linewidth behavior. With naturally square structure and sharp edges, cesium lead halide perovskite nanoplatelet crystals serve as excellent whisper gallery mode microcavities. These cesium lead halide perovskite microcavities exhibit lasing with low threshold ranging from 2.0 μJ/cm2 (peak power density of 2.0 × 107 W/cm2) to 10.0 μJ/cm2 (peak power density of 1.0 × 108 W/cm2) and high quality factor over 3600. Multicolor lasing actions can also be realized by composition engineering in cesium lead halide perovskite crystals, ranging from blue region to red region. By embedding the cesium lead chloride perovskite crystals into two highly reflective distribute bragg reflectors (DBRs), a strong light-matter interaction regime is realized, which is confirmed by the polariton dispersions. With a two coupled oscillator model, a large Rabi splitting energy of ~ 265 meV can be extracted from the polariton dispersion. Under pulsed laser excitations, the CsPbCl3 microcavity exhibits polariton condensation and polariton lasing above a threshold of ~ 12 μJ/cm2 (peak power density of 1.2 × 108 W/cm2). This conclusion is further strengthened by a superlinear power dependence, macroscopic ground-state occupation, the full wavelength at half maximum (FWHM) narrowing, blueshift of the ground-state emission and the build-up of long-range spatial coherence. A transition from strong coupling to weak coupling regime is also observed in CsPbCl3 microcavity, which further confirms the appearance of exciton polariton condensation and exciton polariton lasing. One-dimensional (1D) cesium lead bromide perovskite microcavities are also demonstrated to operate in strong coupling regime. The 1D CsPbBr3 microcavity exhibits low threshold of 0.8 μJ/cm2 (peak power density of 8.0 × 106 W/cm2) for polariton condensation. With the unique 1D structure, the propagation properties of polariton condensates are investigated, showing a high propagation velocity of 10 µm/ps and long-range coherent flow of 60 μm. Through modeling the dynamics of polariton condensate flow, a long lifetime of 3.0 ps is extracted. Our studies on cesium lead halide perovskites expand the semiconductor systems in light matter interactions, which provides considerable promises towards all-optical devices.